TINJAUAN PERSPEKTIF HUKUM ISLAM TERHADAP IMPLEMENTASI PELAKSANAAN TUGAS DEWAN PENGAWAS SYARIAH DI KOPERASI SYARIAH PADA KSPPS BTM BiMU WAY DADI SUKARAME BANDAR LAMPUNG - Fitri Afifah; Muhammad Iqbal Fasa; A. Khumaidi Ja’far (EKSYA : Jurnal Ekonomi Syariah, 2021)
To ensure that there are no deviations from the operational activities of Sharia Cooperatives, Sharia Cooperatives must have an independent internal institution to carry out supervision, called DPS.DPS in carrying out its duties must be optimally and properly in accordance with the regulations that bind it. Because there are still many Sharia cooperative practices that deviate from the regulations regarding the fulfillment of sharia principles themselves. This is because DPS is not optimal in carrying out its duties. The problem in this research is what is the perspective of Islamic law on the implementation of DPS duties?, how is the implementation of the DPS duties in practice in the field and its compliance with the regulations that have been set in Sharia Cooperatives?.The purpose of this study was to determine the perspective of Islamic law on the implementation of DPS duties and to determine the implementation of the implementation of DPS duties in Sharia Cooperatives in practice in the field and their compliance with the regulations that have been set.This research uses the Field Research method or field research. With the research site at KSPPS BTM BiMU Way Dadi Sukarame Bandar Lampung. Data collection techniques used in the form of interviews, observation, and documentation. The analysis was carried out using qualitative methods and a deductive approach.Based on the results of the study, it can be seen that there are 3 regulations that become the reference for DPS at KSPPS BTM BiMU in carrying out their duties, namely; In DSN Decree No. 03 of 2000 concerning Implementation Guidelines for Stipulating Members of the Sharia Supervisory Board, Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 16/Per/M.Kukm/Ix/2015 concerning Implementation of Sharia Savings and Loans and Financing Business Activities, and the Articles of Association of Sharia Cooperatives KSPPS BTM BiMU. In practice, sharia supervision in KSPPS BTM BiMU has not been carried out properly, and is still not optimal.Implementation of the implementation of the duties of the Sharia Supervisory Board in practice in the field and in accordance with the regulations that have been set, some are appropriate and some are not in accordance with the regulations that have been set.